Unbiased Expectations in the MISO Energy Market - Jones, Kevin (International Journal of Energy Economics and Policy, 2026)
This study examines the relationship between spot and forward prices in the Midcontinent Independent System Operator (MISO) wholesale electricity market. I extend existing literature by employing rolling windows and recursive regressions to test to the risk-adjusted unbiased forward rate hypothesis on the MISO exchange. Although risk premiums and downward biased forward prices do exist, I find overall support for the risk-adjusted unbiased forward rate hypothesis. This result differs from previous research on the MISO exchange and may be explained by several factors, including an increase in the number of market participants and production capacity in recent years.